Caracterização Geoquímica de Jazigos Filonianos de Pb-Zn-(Ag) através do Estudo Estatístico dos Teores em Elementos Menores em Sulfuretos - C. Marques de Sá (2010)
Sulfides from Portuguese Vein-type Pb-Zn-(Ag) deposits were analysed with electronic microprobe. The results obtained for several minor elements present in galena and sphalerite were then statistically studied using principal components analysis (PCA). We intend to contribute to the geochemical characterization of these deposits through their contents in the minor elements. We hope to distinguish different subtypes of vein Pb-Zn-(Ag) deposits through the statistical analysis of minor elements present in sulfides